Basics of laser pysics : For students of science and engineering - Renk, Karl F. (Graduate Texts in Physics, 2012)
Basics of Laser Physics provides an introductory presentation of the field of all types of lasers. It contains a general description of the laser, a theoretical treatment and a characterization of its operation as it deals with gas, solid state, free-electron and semiconductor lasers and, furthermore, with a few laser related topics. The different subjects are connected to each other by the central principle of the laser, namely, that it is a self-oscillating system. Special emphasis is put on a uniform treatment of gas and solid-state lasers, on the one hand, and semiconductor lasers, on the other hand. The discussions and the treatment of equations are presented in a way that a reader can immediately follow. The book addresses undergraduate and graduate students of science and engineering. Not only should it enable instructors to prepare their lectures, but it can be helpful to students for preparing for an examination.